Kedelai dan Politik Pangan - Iskandar Andi Nuhung (Forum penelitian Agro Ekonomi, 2013)
EnglishSoybean is one of strategic food crops contributing in the domestic economy, namely enhancing farmers’ income and promoting industry such as tofu, tempeh, and soy sauce, among others. Indonesia is a net importer of soybean to meet its domestic demand. The country only produce soybean around 25 percent of its national consumption. Increases in soybean import price took place in 2008, 2012 and 2013 and made the domestic industry and the government panic. Learning from these experiences, Indonesia has to formulate its food politics in addressing food self sufficiency as a part of food security. Policy, planning and program of food crops development including soybean is not well managed. Predicted soybean production and import volumes show significant differences with the actual ones. Soybean production tends to decrease and soybean import tends to increase since 2004 up to now. Soybean self sufficiency deals with such issues, i.e. low productivity, low technology application, land use competition, high risk, non irrigated areas, price fluctuation, low incentive for investment, and climate change influences. Indonesia should establish market intelligence and formulate a better business environment, land consolidation, sufficient budget allocation, infrastructure development (e.g. irrigation, farm roads, transportation, and economic infrastructure) and better credit access to farmers for food development. The most important issue is returning the authority of food management to the central government to ensure effectiveness of food development which requires commitment from all stakeholders including the government and the parliament. Soybean issue is a good experience useful as a shock therapy and a test case for food management in Indonesia. IndonesianKedelai merupakan salah satu komoditas pangan yang berperan penting dalam perekonomian nasional, merupakan sumber pendapatan petani dan mendorong perkembangan industri seperti industri tahu, tempe, kecap dan industri lainnya. Indonesia termasuk negara yang banyak mengimpor kedelai untuk memenuhi permintaan konsumsi dalam negeri,  karena produksi dalam negeri tidak mampu memenuhi kebutuhan domestik. Produksi kedelai dalam negeri hanya menyumbang sekitar 25 persen dari total kebutuhan nasional yang mencapai sekitar 3,5 juta ton per tahun. Oleh karena itu kenaikan harga kedelai impor, seperti yang terjadi tahun 2008, 2012 dan juga 2013, telah membuat panik industri tahu-tempe dan juga pemerintah. Data dan informasi yang ada menunjukkan bahwa kebijakan dan program pembangunan komoditas pangan termasuk kedelai belum komprehensif dan terkoordinasi secara baik. Realisasi produksi dan volume impor jauh dari proyeksi yang dibuat oleh pemerintah. Swasembada kedelai, misalnya, dihadapkan pada berbagai masalah seperti produktivitas yang rendah, kurangnya aplikasi teknologi, persaingan dalam penggunaan lahan, berisiko tinggi, tergantung air hujan, harga yang fluktuatif, kurangnya insentif untuk investasi dan terjadinya anomali iklim. Indonesia harus mengembangkan intelijen pasar, konsolidasi penggunaan lahan, penyediaan pembiayaan dan kredit untuk pembangunan pangan. Politik pangan yang perlu dipertimbangkan adalah mengembalikan kewenangan urusan pengelolaan pangan kepada Pemerintah Pusat untuk menjamin efektivitas pembangunan pangan nasional. Pembangunan pangan hanya bisa berhasil jika dan hanya jika ada komitmen yang kuat dari seluruh pemangku kepentingan, pemerintah dan parlemen. Kasus dan isu kedelai yang selalu berulang merupakan terapi kejut dan menguji kehandalan pengelolaan pangan nasional.